Population fluctuation of Scolytinae (Coleoptera: Curculionidae) in avocado (Persea americana Mill.) orchards in Michoacán, México - Lázaro-Dzul, Martha Olivia; Equihua-Martínez, Armando; Romero-Nápoles, Jesús; González-Hernández, Héctor; Alvarado-Rosales, Dionicio; Castañeda-Vildózola, Alvaro; Suárez Espinosa, Javier (Revista Colombiana de Entomología, 2023)
This study aimed to determine the population fluctuation of Scolytinae (Coleoptera: Curculionidae) in orchards of avocado Persea americana var. Hass, located in the municipalities of Nuevo San Juan Parangaricutiro (SJ), Uruapan (UR), and Ziracuaretiro (ZR), Michoacán, México. The study was carried out from July 2016 to June 2018. The insects were captured using α-copaene, ethanol and querciverol + ethanol lures, which were placed in bottle traps. The population fluctuation of Scolytinae, during both years and sampling sites, presented its maximum peak during July and August. In ZR, the highest abundance of Scolytinae were recorded during July and October in the 2016-2017 cycle, and during September and October in the 2017-2018 cycle. The population abundance of Scolytinae was higher during the 2016-2017 cycle in SJ and UR, and in ZR the highest population abundance corresponded to the 2017-2018 cycle. The most abundant species of Scolytinae in SJ were Microcorthylus invalidus (43.28 %), Araptus schwarzi (28.68 %) and Corthylus detrimentosus (23.02 %), in UR, were A. schwarzi (41.40 %) and M. invalidus (14.75 %) and ZR were Premnobius cavipennis (26.04 %), Hypothenemus crudiae (17.75 %) and Corthylus flagellifer (16.17%). At the three sites, the maximum population coincided with the periods with higher rainfall and higher relative humidity percentages, conditions that favored a greater availability of food resources at the sites, which were used by the species for their establishment.